2013
DOI: 10.1118/1.4773047
|View full text |Cite|
|
Sign up to set email alerts
|

Correction factors for ionization chamber dosimetry in CyberKnife: Machine‐specific, plan‐class, and clinical fields

Abstract: The differences found between overall correction factors associated with the proposed intermediate calibration fields and the clinical fields under investigation show that depending on the clinical field and the detector used, either a machine-specific reference field or a plan-class specific reference field is more representative for the clinical field. Given the experimental and numerical uncertainties and the small number of clinical fields considered in this study the significance of these observations is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The Exradin A1SL scanning chamber has an active volume of 0.053 cm 3 and an outer diameter of 6.35 mm, and has been previously considered for small field dosimetry . The methods employed in this work mimic the actual methodology employed by clinics to measure point doses in IMRT treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Exradin A1SL scanning chamber has an active volume of 0.053 cm 3 and an outer diameter of 6.35 mm, and has been previously considered for small field dosimetry . The methods employed in this work mimic the actual methodology employed by clinics to measure point doses in IMRT treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the response of the Exradin A1SL scanning‐type ionization chamber (Standard Imaging, Middleton, WI) was investigated in 131 clinical delivery sequences through Monte Carlo simulations. Recent work has shown that many microchamber models may not be suitable for reference dosimetry, whereas many mid‐sized scanning chambers (including the Exradin A1SL scanning chamber) are suitable . For this reason, the Exradin A1SL scanning chamber was chosen as a representative model for this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the second method proposed by Francescon et al [7][8][9] was used to validate the model for the smallest fields. The first method based on the iterative dosimetric data comparison was also recently used by Gago-Arias et al 30 for the Monte Carlo commissioning of a CyberKnife R machine treatment head, but in addition they included comparison with smaller field sizes. Off-axis ratio (OAR MC ), tissue-phantom ratio (TPR MC ), and percentage depth dose (PDD MC ) were calculated.…”
Section: C3 Commissioning Of the Linac Modelmentioning
confidence: 99%
“…However, studies have been conducted to test the precision of EPR/alanine dosimetry for use in the therapeutic dose ranges [3]. The advanced radiotherapy beam modalities and applications that have been verified using alanine dosimetry include intensity modulated radiotherapy (IMRT); electron, proton, carbon ion, and neutron beams radiotherapy; tomotherapy [4]; gamma knife [5]; cyberknife [6]; brachytherapy [7]; small field dosimetry [8]; in vivo dosimetry [9]; electron arc therapy treatment planning verification [10]; total body irradiation [11]; and blood irradiation [12]. In addition, the EPR/alanine dosimetry was used in national audits of radiotherapy centers in other countries, such as the UK [13] and Italy [14].…”
Section: Introductionmentioning
confidence: 99%